Ventricular arrhythmogenic remodelling in diet-induced metabolic syndrome driven by right-to-left regional differences in action potential duration and dominant frequency gradients (2025)
Metabolic syndrome (MetS) has been associated with an increased prevalence of cardiac arrhythmias and sudden cardiac death caused by ventricular fibrillation (VF), but the exact underlying mechanisms are not known. Our aim here was to study the effects that diet-induced MetS produces on ventricular remodelling and its potential electrophysiological arrhythmogenic mechanisms. Thirty-five male NZW rabbits were assigned to a control (n = 16) or MetS group (n = 19), fed for 28 weeks with a high-fat and high-sucrose diet. Echocardiography and electrocardiography were performed before diet and at weeks 14 and 28. Hearts were isolated and perfused in a Langendorff system and epicardial optical mapping was performed using two EMCCD cameras focused on the left (LV) and right (RV) ventricles. mRNA expression levels for ion channel proteins were examined by quantitative RT-PCR. A mixed-model ANOVA and unpaired t test were used for statistical analysis. MetS animals showed LV hypertrophy and electrophysiological abnormalities (increased PQ, QRS, QTc and T wave). In isolated hearts, MetS animals had shorter optical APD90 (action potential duration at 90% repolarization), increased restitution slope and alternans, and faster frequency of activation during VF in the RV, whereas no difference was observed in the LV. The mRNA expression for KvLQT1 and KChIP2 increased in the RV. MetS produced LV hypertrophy, and altered atrioventricular and ventricular conduction and repolarization abnormalities. In isolated hearts, the physiological gradients of refractoriness and frequency of activation during VF were abolished in MetS animals, with fast activation rates in both ventricles, which could be explained, at least in part, by upregulation of KvLQT1 and KChIP2 in the RV. (Figure presented.). Key points: Metabolic syndrome (MetS) has been associated with ventricular arrhythmias and sudden cardiac death, but the exact underlying mechanisms are not known. Previous studies have addressed the effects that individual components of MetS exert, individually, upon electrical cardiac remodelling, but the results obtained in some cases prove inconclusive or contradictory. We investigated the effects of diet-induced MetS on ventricular remodelling and its potential electrophysiological arrhythmogenic mechanisms. We found that diet-induced MetS produced altered activation–repolarization abnormalities as well as fast-activation non-stable flattening of the spatial distribution of dominant frequencies driving ventricular fibrillation, which might be explained, at least in part, due to increased expression of potassium channels in the right ventricle.